Style and Substance. Start-up Pitch Delivery Characteristics as Proxy Metrics for Venture Capitalists' Investment Criteria - Mateusz CODOGNI (Communications of International Proceedings, 2025)
Attracting early-stage investors is vitally important for startup companies. Conversely, finding startups to invest in is vitally important for venture capitalists. And the success of this matchmaking process is important for economy as a whole, contributing to its innovativeness and dynamism. Hence, deepening the understanding of the decision process of early-stage investment is a worthwhile endeavor. Scientific papers pertaining to this subject usually approach it either as a rational process of analysis, or as a process characterized by irrationality, cognitive biases, and swayed by emotions. This paper is an attempt to bridge those two strands of research. It posits that some “irrational” factors of investment decisions may in fact be proxy measurements for rational investment criteria. The paper is based on a narrative literature review and attempts to: 1) identify the rational early-stage investment criteria, 2) identify the “irrational” factors that influence investment decisions, 3) link them together by identifying which of the “irrational” factors can be treated as proxy measurements for which rational decision criteria, 4) hypothesize on further “irrational” factors that have not yet been researched as factors influencing investment decisions, but seem to be good candidates, since they follow from previously identified rational decision criteria. A large group of overlapping known seemingly non-rational factors and known specific rational business project assessment criteria that has been identified, points to the conclusion that this approach finds support in reality and can be fruitful. Also, known specific rational assessment criteria can be used to generate hypotheses pertaining to the existence of further, previously untested, factors that influence the assessment of entrepreneurial pitches.
Keywords: entrepreneurship; startup; pitch; venture capital